PERANCANGAN SISTEM PENGELOLAAN SURAT PERMOHONAN OPD BERBASIS WEB DI PEMERINTAHAN KABUPATEN SITUBONDO - maulana, irvan; Syarif Aminul Khoiri (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
Letters are a formal form of written communication that convey official information, bear legal validity, and serve as a basis for decision-making. The Protocol and Leadership Communication Division (Prokopim) of the Regional Secretariat of Situbondo Regency plays a crucial role in managing official letters, including requests for cooperation (MoU) from Regional Government Organizations (OPD). However, based on observations and interviews conducted during the Field Work Practice (PKL), it was found that the management of MoU request letters is still handled manually, either through printed documents or scattered digital files, making tracking, scheduling, and archiving difficult. This study aims to design a web-based information system for submitting cooperation request letters that can be accessed by all OPDs and centrally managed by the government section. The method used includes field observation, interviews, and system requirements analysis. The proposed system is expected to streamline administrative workflows, improve efficiency, support information transparency, and facilitate decision-making regarding inter-agency cooperation requests within the Situbondo Regency Government.